2021
DOI: 10.3389/fmicb.2021.727434
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dysbiosis Influences Metabolic Homeostasis in Spodoptera frugiperda

Abstract: Insect gut microbiota plays important roles in acquiring nutrition, preventing pathogens infection, modulating immune responses, and communicating with environment. Gut microbiota can be affected by external factors such as foods and antibiotics. Spodoptera frugiperda (Lepidoptera: Noctuidae) is an important destructive pest of grain crops worldwide. The function of gut microbiota in S. frugiperda remains to be investigated. In this study, we fed S. frugiperda larvae with artificial diet with antibiotic mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 59 publications
6
36
0
1
Order By: Relevance
“…The gut microbiota of T. absoluta was dominated by Proteobacteria and Firmicutes at the phylum level, similar to the results of previous studies on lepidopteran insects, including Spodoptera littoralis [ 19 ], Helicoverpa armigera [ 16 ], Plutella xylostella (L.) [ 24 , 53 ], Brithys crini [ 54 ], and Spodoptera frugiperda [ 55 ]. A comparison of the gut bacteria of 30 species of lepidopterans revealed that the most dominant phylum was Proteobacteria [ 56 ].…”
Section: Discussionsupporting
confidence: 85%
“…The gut microbiota of T. absoluta was dominated by Proteobacteria and Firmicutes at the phylum level, similar to the results of previous studies on lepidopteran insects, including Spodoptera littoralis [ 19 ], Helicoverpa armigera [ 16 ], Plutella xylostella (L.) [ 24 , 53 ], Brithys crini [ 54 ], and Spodoptera frugiperda [ 55 ]. A comparison of the gut bacteria of 30 species of lepidopterans revealed that the most dominant phylum was Proteobacteria [ 56 ].…”
Section: Discussionsupporting
confidence: 85%
“…Proteobacteria and Firmicutes have also been reported as dominant taxa in many insects’ gut microbiota, especially in Lepidoptera ( Chen et al, 2020 ; Liu et al, 2020 ). They may function in carbohydrate metabolism, amino acid metabolism, and membrane transport pathways of the host ( Liu et al, 2020 ; Wang et al, 2020a ; Chen et al, 2021 ). In particular, stably colonized gut bacteria may be crucial for insects to adapt to host plants ( Yang et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that an insect's intestinal microbiota is essential for its survival, and plays fundamental roles in development, growth, adaptation, reproduction, and evolution (Y. Chen et al, 2021; Dong et al, 2021). In insects, most symbiotic relationships are based on nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…The insect intestinal microbiota is not only associated with the acquisition of nutrients but plays an important role in the development and maintenance of the host's immune system (Y. Chen et al, 2021; Muhammad et al, 2019). However, the complexity, dynamics, and types of interactions between insects and their intestinal microbiota are not yet fully understood (Q. Ma et al, 2021; Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%